TELAAH NARATIF: PERBANDINGAN PENERAPAN TELEDENTISTRY PADA MASA PANDEMI COVID-19 DI BEBERAPA NEGARA MAJU DAN BERKEMBANG - zilzikridini wijayanti; Iwany Amalliah Badruddin; Melissa Adiatman (Universitas Baiturrahmah, 2022)
Introduction: COVID-19 is an infectious disease and has been declared a public health emergency. This disease can be transmitted through droplets and aerosols. This has an impact on the daily practice of dentistry which is vulnerable to infection when treating patients. Teledentistry can be applied in routine dental practice during the COVID-19 period to prevent direct contact. Patient demand for the application of teledentistry has increased five times during the COVID-19 pandemic, the purpose of this narrative study is to compare the application of teledentistry during the COVID-19 pandemic in developed and developing countries. Methods: This study is a narrative review study. Article searches obtained from Pubmed, EBSCO, and Wiley (n=648) were limited to 2020-2021 in relation to the application of teledentistry during the COVID-19 pandemic in developed and developing countries. We found 33 articles that met the inclusion criteria (n=33), introductory articles, and narrative study guides (n=9), and the total articles used (n=42). Results: The use of teledentistry can be grouped into academic and interdisciplinary learning curricula, postoperative patient follow-up, monitoring of patients due to dentoalveolar trauma, use of dental monitoring for orthodontic treatment, non-emergency conditions, prescribing antibiotics, use of teleradiology, and assisting the practice of departments of oral disease and maxillofacial surgery in several developed and developing countries during the COVID-19 pandemic. Conclusion: The application of teledentistry in developing countries focuses on teleconsultation and non-emergency conditions compared to the application of teledentistry in developed countries which has focused on emergency conditions, dental monitoring for orthodontic treatment, and postoperative patient follow-up.